MENGGUGAH FONDASI KEILMUAN ILMU HUKUM DALAM PENGAKUAN PERKAWINAN HOMOSEKSUAL DI MASSACHUSETTS MELALUI EFISIENSI EKONOMI - Sugianto, Fajar; Budiarsih, Budiarsih (DiH: Jurnal Ilmu Hukum, 2018)
Law and economics are two independent sciences that compliment each other in analyzing forms of legal issues. The limitations of each independent sciences in fact have brought these two came even closer in resolving the issue of the legalization of homosexual marriages in Massachusetts. As a scientific method, Law and Economics, also known as the economic analysis of law, explores the law and jurisprudence in new ways through different dimensions. The use of economics broaden the field of law especially as a tool to create incentives to change human behavior in achieving its objectives based on its idealism of efficiency. The use of Law and Economics in this writing provided economic rationales that the legalization of homosexual marriages in Massachusetts are efficient therefore the law shall produce rules that lead to the most efficient change that the society desire the most.